Analysis of Factors Causing Noncompliance with Medical Record File Destruction Scheduling at Kalabahi Regional Hospital - Olidela, Imanuel Nikson; Wijayanti, Rossalina Adi; Nuraini, Novita; Muflihatin, Indah (International Journal of Healthcare and Information Technology, 2025)
Destruction of medical records has not been carried out at Kalabahi Regional Hospital, resulting in the accumulation of medical record files that are not properly placed on storage shelves. This study aims to analyze the factors contributing to the mismatch in the scheduling of record destruction at Kalabahi Regional Hospital, based on the MOA (Motivation, Opportunity, Ability) performance theory. This research employed a qualitative approach, with problem-solving recommendations developed through brainstorming. The subjects in this study included the Head of the Medical Records Installation, the Head of the Medical Records Committee, and three filing officers. Data were collected through in-depth interviews, observation, documentation, and brainstorming sessions. Data validity was ensured using technique triangulation and source triangulation. The results of the study, based on the MOA performance theory, showed: Motivation factors included the absence of praise or reprimands from the head of the medical records installation to staff related to destruction activities. Opportunity factors included the lack of a designated room for destruction activities, insufficient filing shelves, the absence of an SOP for destruction, the absence of a dedicated destruction team, the lack of job descriptions for the destruction team, no budget planning for destruction activities, no preservation list, and no destruction tools. Ability factors included the officers' lack of practical skills and knowledge about destruction activities. Based on these findings, it is recommended to plan and implement training programs, provide praise and reprimands to filing staff regarding destruction activities, provide a designated room for destruction, increase the number of filing shelves, develop an SOP for destruction, establish a dedicated destruction team along with clear job descriptions, and allocate a budget for destruction activities.